2016
DOI: 10.1111/jphp.12555
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endothelial NO synthase by a xanthine derivative ameliorates hypoxia-induced apoptosis in endothelial progenitor cells

Abstract: KMUP-1 inhibited hypoxia-induced dysfunction and apoptosis in EPCs, which may be mediated through suppressing oxidative stress, upregulating eNOS and downregulating the caspase-3 signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…In addition, baicalin suppressed oxidative activity in the endplate chondrocytes induced by H 2 O 2 , via effectively reducing levels of MDA, increasing levels of SOD, and elevating NO activities (5,9,22). eNOS, an enzyme which activates the expression of NO (23)(24)(25), was also shown to be increased following pretreatment with baicalin, which suggested that baicalin also inhibited the apoptosis through upregulating the expression of eNOS.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, baicalin suppressed oxidative activity in the endplate chondrocytes induced by H 2 O 2 , via effectively reducing levels of MDA, increasing levels of SOD, and elevating NO activities (5,9,22). eNOS, an enzyme which activates the expression of NO (23)(24)(25), was also shown to be increased following pretreatment with baicalin, which suggested that baicalin also inhibited the apoptosis through upregulating the expression of eNOS.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, TRPC3 could provide an additional source of Ca 2+ for eNOS stimulation, as recently shown in porcine coronary artery endothelial cells (PCAECs) (Huang et al, ). As anticipated above, besides stimulating EPC egression from BM, NO controls EPC‐dependent angiogenesis and vascular remodeling by promoting proliferation and migration and inhibiting apoptosis (Bai et al, ; Lu et al, ; Ozuyaman et al, ; Wu et al, ; Zuccolo, Bottino, et al, ). The up‐regulation of NO synthesis by exogenously expressed TRPC3 could be even more therapeutically relevant in ECFCs.…”
Section: Introductionmentioning
confidence: 93%
“…Of note, endogenous nitric oxide (NO), as a paracrine pro-angiogenic signaling molecule, is primarily synthesized by endothelial nitric oxide synthase (eNOS) and released from EPCs or mature endothelial cells during neovascularization [15,16]. It is well known that NO could improve EPCs' and endothelial cells' migration, angiogenesis, and resistance to apoptosis [17][18][19], and therefore, NO release contributes to the paracrine properties of EPCs during tissue neovascularization.…”
Section: Introductionmentioning
confidence: 99%